The hibernating heart: reversible left ventricular dysfunction in chronic heart failure. Issue 885 (1st July 1999) - Burn, Steven; Walters, Mark; Caplin, John
Abstract : A patient with severe heart failure secondary to coronary heart disease is presented. Following investigation he was thought to have significant areas of myocardial hibernation and was therefore treated with coronary revascularisation, with major clinical benefit.